2021
DOI: 10.1055/s-0041-1732371
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thrombosis and Bleeding in Patients with Severe COVID-19 versus Other Viral Pneumonias in the Context of Extracorporeal Membrane Oxygenation

Abstract: Letter to the EditorThis document was downloaded for personal use only. Unauthorized distribution is strictly prohibited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 11 publications
0
18
2
Order By: Relevance
“…Thrombosis incidence was lower than bleeding in our cohort, which contrasts with the recent ELSO report on VV-ECMO [12], even though our study included deep vein thrombosis and pulmonary embolism/thrombosis which are not recorded in the ELSO registry. Our results also differ from the high rates of thrombosis in early reports of COVID-19 patients on VV-ECMO [27,28,34]. Two factors might have influenced these results.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Thrombosis incidence was lower than bleeding in our cohort, which contrasts with the recent ELSO report on VV-ECMO [12], even though our study included deep vein thrombosis and pulmonary embolism/thrombosis which are not recorded in the ELSO registry. Our results also differ from the high rates of thrombosis in early reports of COVID-19 patients on VV-ECMO [27,28,34]. Two factors might have influenced these results.…”
Section: Discussioncontrasting
confidence: 99%
“…Second, thrombosis reporting is highly dependent on clinical and radiological screening protocols. Systematic ultrasound or computed-tomography assessment of thrombosis on ECMO is likely accountable for the discrepancy between our results and recently published COVID-19 reports, especially regarding pulmonary embolism/thrombosis [27,28,34].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The overall in-hospital mortality varied widely across included studies; the lowest was 15.1% and the highest was 80.8%, as well as the pooled estimate was 40.3% (95% CI: 33.1%–47.5%, p < 0.001, 12 studies, 2 , 20 - 30 6039 patients) ( Figure 4 ). Eight 20 , 22 , 23 , 25 28 , 30 studies reported the use of anticoagulants during ECMO, with most patients receiving unfractionated heparin (UFH). The use of argatroban was mentioned for heparin-induced thrombocytopenia in two studies.…”
Section: Resultsmentioning
confidence: 99%